2020
DOI: 10.1002/ehf2.12682
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular mechanical pattern in patients undergoing mitral valve surgery: a predictor of post‐operative dysfunction?

Abstract: Aims The PREPARE-MVR study (PRediction of Early PostoperAtive Right vEntricular failure in Mitral Valve Replacement/Repair patients) sought to investigate the alterations of right ventricular (RV) contraction pattern in patients undergoing mitral valve replacement/repair (MVR) and to explore the associations between pre-operative RV mechanics and early post-operative RV dysfunction (RVD). Methods and resultsWe prospectively enrolled 42 patients (63 ± 11 years, 69% men) undergoing open-heart MVR. Transthoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…The results of the intra- and interobserver variability and reliability analyses are summarized in Tables 1 , 2 . Reproducibility of global EDV, ESV, and decomposed ESVs were high, which is consistent with our previous reports using the earlier versions of the ReVISION software ( 10 , 11 , 13 ). Regarding the 15 segments, a smooth base-to-apex gradient could be observed ( Table 2 , Figures 6 , 7 ), with the inflow tract and basal segments having the lowest variability and the highest reliability and free wall apical segments exhibiting the highest variability and the lowest reliability.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the intra- and interobserver variability and reliability analyses are summarized in Tables 1 , 2 . Reproducibility of global EDV, ESV, and decomposed ESVs were high, which is consistent with our previous reports using the earlier versions of the ReVISION software ( 10 , 11 , 13 ). Regarding the 15 segments, a smooth base-to-apex gradient could be observed ( Table 2 , Figures 6 , 7 ), with the inflow tract and basal segments having the lowest variability and the highest reliability and free wall apical segments exhibiting the highest variability and the lowest reliability.…”
Section: Resultssupporting
confidence: 91%
“…For this purpose, we developed the Right VentrIcular Separate wall motIon quantificatiON (ReVISION) method a few years ago, which is a 3D echocardiography (3DE)-based solution for the quantification of the relative contribution of longitudinal, radial, and anteroposterior shortening to global RV EF (9). Since then, our technology has been applied in several clinical scenarios (10)(11)(12), and the strengths of the ReVISION method have been demonstrated in the in-depth characterization of RV mechanical pattern and the prognostication of patients even in the face of maintained RV EF (13). The ReVISION method and the associated online platform (demo version available at https://www.revisionmethod.com) are improved continuously, and recently, various new features, such as the assessment of longitudinal, circumferential, and area strains have been implemented to enable the convenient, standardized, and more comprehensive analysis of RV function using 3DE datasets.…”
Section: Introductionmentioning
confidence: 99%
“…23 However, several studies have contradicted these observations, highlighting the potential importance of the ''bellows'' action (radial shortening) and anteroposterior shortening in healthy individuals and in patients with cardiovascular diseases as well. 7,16,24,25 Although the longitudinal motion of the tricuspid annulus appears to be quite prominent, it is important to emphasize that because of its large surface, even subtle inward motion of the RV free wall can result in a considerable amount of volume change. 26 Nevertheless, current clinical practice lacks any RV functional parameter, which selectively represents the nonlongitudinal motions of the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…There is an instantaneous shift in the RV contraction at the opening of the pericardial sac: as normal pericardial constraint vanishes the longitudinal shortening will significantly decrease; however, global EF remains maintained due to effective compensation by the radial motion. A recent follow-up study in patients underwent mitral valve replacement or repair confirmed the temporary nature of this phenomenon as 6-months later the normal relative contribution of the aforementioned wall motion directions was restored [26]. Heart transplanted patients represent quite a different patient subpopulation, as the dominance of radial motion seems long-lasting and parameters referring only to longitudinal shortening will report dysfunction for quite a long time after the operation ( Fig.…”
Section: Role and Relative Contribution Of Different Components Of Thmentioning
confidence: 85%